2007
DOI: 10.3174/ajnr.a0859
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Extravasation on CT Predicts Mortality in Primary Intracerebral Hemorrhage

Abstract: BACKGROUND AND PURPOSE:Recent studies of intracerebral hemorrhage (ICH) treatments have highlighted the need to identify reliable predictors of hematoma expansion. The goal of this study was to determine whether contrast extravasation on multisection CT angiography (CTA) and/or contrastenhanced CT (CECT) of the brain is associated with hematoma expansion and increased mortality in patients with primary ICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
117
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(122 citation statements)
references
References 24 publications
5
117
0
Order By: Relevance
“…46 However, this sign is not standardized, and interobserver agreement is unknown. In a study of contrast extravasation within primary ICHs, Kim et al 23 found the swirl sign to be predictive of mortality in univariate analysis but only extravasation remained significant in subsequent multivariate analysis. The predictive value of this sign in extra-axial hematomas has also been questioned in another study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…46 However, this sign is not standardized, and interobserver agreement is unknown. In a study of contrast extravasation within primary ICHs, Kim et al 23 found the swirl sign to be predictive of mortality in univariate analysis but only extravasation remained significant in subsequent multivariate analysis. The predictive value of this sign in extra-axial hematomas has also been questioned in another study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports examining extravasation in spontaneous intracerebral hematomas have advocated the use of delayed imaging to maximize sensitivity for extravasation identification. 12,15,22,23 Ederies et al 15 showed that absolute and mean hematoma expansion were greater in CTA-negative PCL-positive patients compared with CTA-and PCL-negative patients. These results must, however, be measured against the decreased specificity of extravasation seen on delayed imaging and the overshadowing effect of extravasation identified on CTA (CTA-spot sign) over PCL for hematoma-growth prediction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Several reports proposed the CT angiography spot sign as a radiological marker predictive of HE in the acute setting. [2][3][4][5][6] Although the general assumption is that spot sign is the radiological correlate of active bleeding at the site of vessel rupture, its exact pathology is not known. A modest positive predictive value of 61% to predict HE 6 suggests that spot sign may be present even when bleeding has ceased, perhaps representing a site of arrested hemorrhage or associated microvascular lesion such as a microaneurysm.…”
mentioning
confidence: 99%
“…The prevalence of the CTA spot sign decreases as time from onset to CTA increases, but its presence remains predictive of hematoma expansion independent of time from onset to CTA [36,38]. Several other studies showed that the CTA spot sign is predictive of mortality and poor outcome [45,46]. In secondary ICH, the CTA spot sign is also predictive of in-hospital mortality [47], but vascular and nonvascular mimics of this finding are common and lower its sensitivity and specificity [48].…”
Section: Ct Angiographymentioning
confidence: 99%